The Materials for Sensitive Elements of Angular Velocity Sensors on Bulk Acoustic Waves - Durukan, Yasemin; Shevelko, Michail M.; Peregudov, Alexandr N.; Popkova, Ekaterina S. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
The criteria for the selection of the materials of the plate piezoelectric transducers and the acoustic duct of the sensitive element of the angular velocity sensors are determined. The following materials are considered for piezo plates: quartz (SiO 2 ), lithium niobate (LiNbO 3 ) and lithium tantalate (LiTaO 3 ), as well as langasite (La 3 Ga 5 SiO 14 ). Based on the method proposed earlier by the authors, the optimal cuts for shear wave excitation are found. As the materials of the acoustic duct, quartz, chalcogenide glasses, and several single crystals are considered. As a result, the materials, which provide the optimal design of the sensitive element, are revealed.